Characteristics of us adults attempting tobacco use cessation using e-cigarettes. (January 2020) - Chido-Amajuoyi, Onyema Greg; Mantey, Dale; Cunningham, Sonia; Yu, Robert; Kelder, Steven; Hawk, Ernest; Cinciripini, Paul; Shete, Sanjay
Abstract: Background: Use of e-cigarettes for tobacco cessation efforts is a growing trend in the United States. However, little is known about the factors that determine the use of e-cigarettes for this specific purpose. Methods: This study examined current and former cigarette smokers that reported ever using e-cigarettes. Data were obtained from a 2018 Texas population health assessment survey ( n  = 569) and weighted to be representative to Texas. A multivariable logistic regression was used to assess the socio-demographic and behavioral correlates of using e-cigarettes for tobacco cessation. Results: Overall, 41.3% of e-cigarette users reported using them for tobacco cessation. Among ever e-cigarette users, Non-Hispanic blacks (aOR: 0.21; 95% CI, 0.07–0.64), males (aOR: 0.40; 95% CI, 0.20–0.80), and individuals not confident in obtaining health information (aOR: 0.38; 95% CI, 0.15–0.96) were less likely to use e-cigarettes for tobacco use cessation. Conversely, among ever e-cigarette users, odds of using e-cigarettes for tobacco cessation were higher among those who were 35–44 years old (aOR: 3.68, 95% CI: 1.26–10.71), those who received advice to quit smoking from a healthcare professional (aOR: 2.77, 95% CI, 1.36–5.64), and those with more than 5 years since their last routine checkup (aOR: 3.91; 95% CI, 1.23–12.45). Conclusion: Findings from this study suggest that both health behaviors and sociodemographic factors predict use of e-cigarettes for the purpose of tobacco cessation. Furthermore, the relationship between use of e-cigarettes as a cessation device and being advised to quit tobacco use by a healthcare professional calls for additional investigation. Highlights: Use of e-cigarettes for the purposes of tobacco use cessation is common. Sociodemographic characteristics predict use of e-cigarettes for cessation. Health behaviors are associated with use of e-cigarettes for cessation. Cessation advice by physician increased odds of quit attempts using e-cigarettes. Nearly two-thirds of those advised to quit smoking made efforts using e-cigarettes.